Realitas Media Massa Lokal dan Politik Dalam Proses Demokrasi di Kota Langsa - Arisandy, Danil Putra (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2023)
Mass media has a very important role in distributing information to society, which is part of democracy. However, in carrying out its function as social control, the media has limitations, and the media also has a relationship with local authorities. The local authority, which we call the government, will try to build relationships with the media to build the government's image through reporting in local media. This study is qualitative research that uses a content analysis approach. The use of qualitative research is related to the nature of the data collected, which is an exploration of meaning, experiences, and phenomena related to local mass media in Langsa. Through qualitative data, this research attempts to analyze the relationship between mass media and politics in Langsa City during the reporting process. The research object is focused on online news in Langsa City, such as Tanyoe Langsa, Chapnews.com, and Beritalima.com in Langsa, and Serambi.com, online People's Thoughts, Online People's Daily, and political figures. The research results show that the mass media has a strong relationship with the government, so it tends to provide news that supports government policies and programs. The mass media, BeritaLima.com, TanyoLangsa, and Chapnews, have a role that tends to support the government in reporting due to the relationships that are formed. Therefore, the mass media needs to strive to maintain editorial independence and freedom in presenting accurate, balanced information and prioritizing its role as a government watchdog in the democratic process.